Sonographic measurement of subarachnoid space and ventricular width in premature and mature newborns (Annals of Medical Research, 2021)
Aim: We aimed to measure the subarachnoid space and ventricular width with transfontanel sonography in premature and mature newborns and to identify the subarachnoid space/ventricular width ratio.